Usefulness of Contents of Changi Kheti Magazine as Perceived by the Readers in Ludhiana District of Punjab - Kaur, Manjot; Kaur, Sukhjeet (Indian Journal of Extension Education, 2012)
Thirty six issues of Changi Kheti magazine published by Punjab Agricultural University from July 2008 to June 2011  were taken up for the purpose of quantitative analysis of contents. A sample of 50 individual life members and their  spouses (50) of Ludhiana district was selected proportionately. The data were collected with the help of interview  schedule. The study revealed that contents of the selected magazine articles, miscellaneous items, photographs, success  stories, advertisements, editorials and illustrations occupied the space in the descending order. About 64 per cent of the  respondents desired that the articles related to 'plant protection & pest management' should be published in all the twelve  issues of this magazine, while only one respondent reported the need for publishing articles on 'agriculture engineering' in  all the twelve issues of this magazine. It was concluded that association between the profile of the readers and the  usefulness of the contents of Changi Khetimagazine was non-significant.
Keywords: Communication; Transfer of Knowledge; Changi Kheti